The role of emotional marketing in enhancing strategic customer behavior through financial knowledge: An analytical study of a sample of shopping malls in Iraq - Meala, Qhayser Ali Hadi; Al Zubaidi, Haidar Hamoudi Ali; Al-Daamee, Waleed Abbas Jebur (Edelweiss Applied Science and Technology, 2024)
The research aims to diagnose the logical relationships between emotional marketing and its role in enhancing strategic customer behavior through financial knowledge to reach results in the dynamic environment of shopping malls. The paper was designed in light of adopting the descriptive analytical approach to variables and collecting data and information through the questionnaire tool distributed to the shopping malls of the research sample. Using statistical analysis programs to reach the results, the study sample reached (25) shopping malls in the local environment of the country. The results showed that there is a threat in the local environment in which these malls operate through the entry of foreign investment projects in this field, which led to an increase in supply and competition in terms of quality, prices and delivery services to gain customers. The studied malls had to develop a strategy on how to attract and retain customers by using emotional marketing practices and relying on financial knowledge to influence strategic customer behavior, as the current and future customer has become rapidly changing in tastes, needs, desires and transformation through technological development and the world has become a small village that can be viewed at any time and in short periods of time. The research also concluded that the threat of new investment through the establishment of new malls as new investment projects affects supply and demand in the environment in which these studied malls operate. The research also concluded that there is a correlation and influence relationship between the research variables of the studied malls, which includes a package of results that benefit the research community. The paper aims to bridge the knowledge gap between the variables of the paper in the dynamic environment by using emotional marketing as a competitive tool in influencing strategic customer behavior through financial knowledge to gain and maintain the current customer and gain the potential customer.